COVID-19 and the athletic heart: emerging perspectives on pathology, risks and return to play - Kim, J. H.; Levine, B. D.; Phelan, D.; Emery, M. S.; Martinez, M. W.; Chung, E. H.; Thompson, P. D.; Baggish, A. L. (JAMA Cardiology, 2020)
Importance Cardiac injury with attendant negative prognostic implications is common among patients hospitalized with coronavirus disease 2019 (COVID-19) infection. Whether cardiac injury, including myocarditis, also occurs with asymptomatic or mild-severity COVID-19 infection is uncertain. There is an ongoing concern about COVID-19-associated cardiac pathology among athletes because myocarditis is an important cause of sudden cardiac death during exercise.